Oxidative Stress and Psychiatric Disorders: Evidence from the Bidirectional Mendelian Randomization Study - Zhe Lu; Chengcheng Pu; Yuyanan Zhang; Yaoyao Sun; Yundan Liao; Zhewei Kang; Xiaoyang Feng; Weihua Yue (MDPI AG, 2022)
Observational studies have shown that oxidative stress is highly related to psychiatric disorders, while its cause-effect remains unclear. To this end, a Mendelian randomization study was performed to investigate the causal relationship between oxidative stress and psychiatric disorders. On the one hand, all causal effects of oxidative stress injury biomarkers (OSIB) on psychiatric disorders were not significant (p > 0.0006), while the findings suggested that part of OSIB was nominally associated with the risk of psychiatric disorders (causal OR of uric acid (UA), 0.999 for bipolar disorder (BD), and 1.002 for attention-deficit/hyperactivity disorder (ADHD); OR of catalase was 0.903 for anorexia nervosa (AN); OR of albumin was 1.162 for autism; p < 0.05). On the other hand, major depressive disorder (MDD) was significantly associated with decreased bilirubin (p = 2.67 × 10−4); ADHD was significantly associated with decreased ascorbate (p = 4.37 × 10−5). Furthermore, there were also some suggestively causal effects of psychiatric disorders on OSIB (BD on decreased UA and increased retinol; MDD on increased UA and decreased ascorbate; schizophrenia on decreased UA, increased retinol and albumin; ADHD on increased UA, and decreased catalase, albumin, and bilirubin; AN on decreased UA). This work presented evidence of potential causal relationships between oxidative stress and psychiatric disorders.